Electrochemical Characteristics of Polyaniline Nanofibers and Active Chromium Sulfide Nanoparticles for Asymmetric Supercapacitor Applications. Issue 9 (28th February 2023) - Iqbal, Hifza; Nazim, Amina; Haq, Mahmood Ul; Hassan, Ather; Mahmood, Sajid; Muhammad, Zahir; Iqbal, Muhammad Faisal
Abstract: Metal sulfides exhibit rich surface chemistry and electrochemical features and their comparison with polyaniline may give a new perspective to supercapacitor applications. Active chromium sulfide nanoparticles and polyaniline nanofibers were synthesized using the solvothermal and polymerization process, respectively. Chromium sulfide nanoparticles reveal a good specific capacitance of 594.38 F/g at the current density of 1 mA/cm 2, meanwhile, the polyaniline nanofibers exhibit a maximum specific capacitance of 150 F/g at the current density of 4 mA/cm 2, through the galvanostatic charge‐discharge profile. The power density of the polyaniline was found 3111 W/Kg, which is greater due to the conductive nature of polyaniline, meanwhile, chromium sulfide nanoparticles also exhibit a reasonable power density of 2403.06 W/Kg. Comparatively, chromium sulfide nanoparticles maintained specific capacitance and power density. The two electrodes asymmetric system exhibits a good coulomb efficiency of 100 % at 1 mA/cm 2 . So, chromium sulfide nanoparticles exhibit good electrochemical characteristics for supercapacitor applications. Abstract : Active chromium sulfide nanoparticles show a good Csp of 684.90 F/g through CV and Csp of 594.38 F/g through GCD. Polyaniline nanofibers exhibit a power density of 3111 W/Kg at the current density of 8 mA/cm 2 . The two electrodes asymmetric system exhibits a good coulomb efficiency of 100 % at the 1 mA/cm 2 . Comparatively, active chromium sulfide nanoparticles maintained the Csp and power density.